PENGARUH KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI KOPERASI PEGAWAI BANK INDONESIA (KOPEBI) - Tiffany Veronica Bakara; Tine Yuliantini (Universitas Mercu Buana, 2021)
This research aims to know the influence of Compensation of Work Motivation, and Work Environment on Employee Performance. The object of this research is employees who work at Koperasi Pegawai Bank Indonesia (KOPEBI) located in Central Jakarta. The study was conducted on 65 respondents using quantitative descriptive. The sampling method uses the saturated sample technique. Data collection methods using survey methods, with research instruments is a questionnaire. Data analysis method uses Partial Least Square. The results of this study indicate that the Work Motivation, and Work Environment Compensation variables show a positive and significant impact on Employee Performance at Bank Indonesia Employee Cooperatives (KOPEBI).